Resource Linkages to Poverty among Scheduled Castes in District Ghazipur, UP: A Geographical Perspective - Mridul, Ajay Raj; Mishra, Anand Prasad (National Geographical Journal of India, 2022)
Poverty as complex social phenomenon has multi-dimensional linkages towards assets and resources. Resources are the major geographical elements that shaped and reshaped the pattern of poverty in underdeveloped regions. In traditional and historically graded society uneven distribution and lower reach of resources to Scheduled castes people impacted poverty in a greater way. It needs in-depth investigation that established proper linkages in between resources and poverty. Study of resource and poverty relationship in hierarchal and exploitative structured society is more significant in order to draw logical conclusion on poverty. In present research authors tried to find out relationship between resource distribution, its reach and human poverty for Scheduled Castes (SCs) population. The present attempt by authors is based on primary data that collected through field observation with the help of scheduled questionnaire.